A DNA Damage Response Related Signature to Predict Prognosis in Patients with Acute Myeloid Leukemia. (16th March 2023) - Wang, Jun; Wu, Jiafei; Wang, Yijing; Wang, Yu; Jiang, Chuanyan; Zou, Mengying; Jin, Xiaokang; Sun, Xiaoran; Zhang, Yu; Ma, Sijia; Wang, Guoqiang; Zhu, Xin; et al.
Abstract: The prognosis of acute myeloid leukemia (AML) is disappointing in most subtypes and varies widely. DNA damage response (DDR) is associated with prognosis and immunotherapy in multiple cancers. Here, we identify a signature of eight DDR-related genes associated with overall survival, which stratifies AML patients into high- and low-risk groups. Patients in low-risk group were more likely to respond to sorafenib. The signature could be an independent prognostic predictor for patients treated with ADE and ADE plus gemtuzumab ozogamicin. Therefore, this DDR prognostic signature might be applied to prognostic stratification and treatment selection in AML patients, which warrants further studies.